Evaluation of local scour depth around complex bridge piers - Castiblanco, M. (2012)
The main objective of this study is to evaluate and compare three available methods for the prediction of the local scour depth around complex bridge piers using new experimental data. The complex pier model used in the study was embedded in uniform diameter (0.86 mm) sand. A total of 9 tests were carried out in a 40 m long and 2 m wide rectangular sand-bed tilting flume. Tests lasted between 15 and 25 days, for a variety of pile cap positions relative to the initial bed under steady clear-water flow conditions. The comparison of predictions with measurements, including some selected from the literature, allows stating that the HEC-18, Auckland and Florida methods potentially lead to both overestimations and underestimations, depending on the relative position of the pile cap. It became obvious from the study that differences may be influenced by the test stop criterion adopted in the experiments.